Modelo de leitura para indexação de fotografias baseado no método complexo e nas funções primárias da imagem - Gislene Rodrigues da Silva (2018)
This research has as a premise to reflect on the "Complex Method" and the "Primary Functions of the Image" proposed by Català Domènech (2011) and to evaluate the contribution of these principles to the understanding of the content of the photographs during the indexing process. The elaboration of this research is justified by the necessity of the development of studies that contemplate elements that portray the complexity in which the photographs are currently as an information resource in the virtual environment. Moreover, at the moment of indexing, it is necessary to consider aspects such as the context of creation, the point of view of the author and the spectators as well as the emotions and feelings that images can provoke and transmit. This research had as objective to analyze if the use of the "Complex Method" and the "Primary Functions of the Image" proposed by Català Domènech (2011) can contribute to the selection of keywords in the process of indexing the photographs, proposing the application of two matrices. Such matrices were elaborated as Reading Model for Photographs Indexing based in Complex Method and Primary Functions of the Image. In this sense, the first matrix allowed to obtain information about the photographs of the sample and also provided subsidies for the filling of Matrix 2. The second matrix was elaborated to fill the keywords resulting from the application of the indexing questions formulated on the basis of the "Primary Functions of the Image "and also in the information obtained by Matrix 1. In the application of the model were indexed five photographs of the free image bank Pixabay. The application of the proposed model was performed by the author of this research without the use of controlled vocabulary. As results we can verify that the proposed model was applicable to all the photos and made the indexation more exhaustive than the one available by the image bank. In addition, it was observed that this model offered important elements for use at the moment of the indexing of the photographs, especially those linked to the subjectivity and the interpretation of the images.